Poor urban infrastructure and civic mess in Indian cities - Kataria, S.K. (2011)
The pace of economic growth has, as expected, led to an increase in urbanisation as cities provide larger opportunities for individual activity. But in the bargain people have to come to grips with inadequate civic amenities, which cause severe hardship to them. The burgeoning migration and population have taken their toll on the civic infrastructure systems like water supply, sewerage, drainage, shelter and public transport besides flora and fauna. The state of urban infrastructure suffers from weak or outmoded urban management, outdated planning and delivery models. The need of the day is a pragmatic municipal autonomy and an urban management and governance structure that is founded on the modern day requirements and is capable of taking future development realities in its stride. - Reproduced.
Keywords: Urbanization - India; Urbanization